2021
DOI: 10.3390/jrfm14100465
|View full text |Cite
|
Sign up to set email alerts
|

Assess the Impact of the COVID-19 Pandemic and Propose Solutions for Sustainable Development for Textile Enterprises: An Integrated Data Envelopment Analysis-Binary Logistic Model Approach

Abstract: The COVID-19 pandemic impacted many socio-economic areas of countries around the world. It has made the production and business situations of enterprises face substantial difficulties. In this study, the authors used data envelopment analysis (DEA) models to assess the impact of the COVID-19 pandemic on Vietnam’s textile and garment enterprises. The authors have used the binary logistic model to determine the factors affecting employees’ decision to change jobs in the textile industry. The research results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Impact of the quarantine regime on the level of investments according to the sector. References (Adnan and Hasan 2021;Ali et al 2022;Asteriou et al 2023;Clark et al 2021;González and Gallizo 2021;Hasnaoui et al 2021;Huynh et al 2021;Kurien ė 2022;Liedtke 2021;Liu et al 2022;Lutfi et al 2022;Nguyen and Vu 2021;Nikolajenko et al 2021;Pileckait ė and Subačien ė 2023;Pourmansouri et al 2022;Rahman et al 2022;Ramachandran et al 2021;Raza et al 2022;Senkus et al 2022;Shabir et al 2023;Simoens and Vander Vennet 2022;S ūdži ūt ė and Jakubavičius 2022;Toth et al 2022;Wulandari et al 2022;Zheng and Zhang 2020;Žinyt ė and Jurkonien ė 2023) are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Impact of the quarantine regime on the level of investments according to the sector. References (Adnan and Hasan 2021;Ali et al 2022;Asteriou et al 2023;Clark et al 2021;González and Gallizo 2021;Hasnaoui et al 2021;Huynh et al 2021;Kurien ė 2022;Liedtke 2021;Liu et al 2022;Lutfi et al 2022;Nguyen and Vu 2021;Nikolajenko et al 2021;Pileckait ė and Subačien ė 2023;Pourmansouri et al 2022;Rahman et al 2022;Ramachandran et al 2021;Raza et al 2022;Senkus et al 2022;Shabir et al 2023;Simoens and Vander Vennet 2022;S ūdži ūt ė and Jakubavičius 2022;Toth et al 2022;Wulandari et al 2022;Zheng and Zhang 2020;Žinyt ė and Jurkonien ė 2023) are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Taşdemir (2020) measured efficiency with the DEA method in the aviation sector, which is one of the sectors most affected by the Covid-19 pandemic. Nguyen and Vu (2021) measured efficiency on textile companies of Vietnam with DEA method. Kim and Choi (2021) investigated the impact of the Covid-19 pandemic on the productivity of the leading Asian sea container ports with the DEA method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some relevant research methods related to textile and garment are shown in Table 1. The DEA was used to assess performance, the CCR model was used to calculate the total efficiency score, the BBC model was used to assess the technical efficiency scale, and the SBM model was used to evaluate the efficiency ranking, as well as the delay problems of DMUs, in [8,[31][32][33][34][35]. As mentioned in [36,37], the DEA window model was used by the original DEA model, which explored the trend of DMUs over time with multiple input and output variables; this is beneficial when dealing with small sample sizes.…”
Section: Textile and Garment Industry Related Researchmentioning
confidence: 99%
“…As mentioned in [36,37], the DEA window model was used by the original DEA model, which explored the trend of DMUs over time with multiple input and output variables; this is beneficial when dealing with small sample sizes. As can be shown in [35,36,38,39], to measure the change in total factor productivity, the Malmquist-DEA model was used, including changes in technical efficiency and change in technology change. Multicriteria decision models, such as the analytical hierarchy process (AHP) [40][41][42] and the technique for order of preference by similarity to ideal solution (TOPSIS) [43,44], are widely used to assess the performance of the textile and garment industry.…”
Section: Textile and Garment Industry Related Researchmentioning
confidence: 99%